2021
DOI: 10.2147/ppa.s323846
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Patients’ Attitudes Toward Deprescribing and Their Perception of Pharmacist Involvement in a European Country: A Cross-Sectional Study

Abstract: Purpose To explore how adult patients perceive deprescribing in a country with developing pharmaceutical care. Patients and Methods This was a multicenter cross-sectional study conducted in ten community pharmacies across Croatia. Community-dwelling adults 40 years and older, taking at least one prescription medication long term, were invited to participate. The revised and validated Patients’ Attitude Towards Deprescribing Questionnaire was used to investigate communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 54 publications
6
24
2
Order By: Relevance
“…In our study, the willingness to have a medication deprescribed was signi cantly associated with two factors: a higher value for the involvement factor for both older adults and caregivers, as well as a low value for the concern about stopping factor, only for older adults. These results were also found in a cross-sectional study conducted in Croatia [27]. Indeed, participants who want to be involved in discussions regarding medication management and who have fewer concerns about drug discontinuation, are probably more likely to be open to deprescribing.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In our study, the willingness to have a medication deprescribed was signi cantly associated with two factors: a higher value for the involvement factor for both older adults and caregivers, as well as a low value for the concern about stopping factor, only for older adults. These results were also found in a cross-sectional study conducted in Croatia [27]. Indeed, participants who want to be involved in discussions regarding medication management and who have fewer concerns about drug discontinuation, are probably more likely to be open to deprescribing.…”
Section: Discussionsupporting
confidence: 57%
“…The revised Patients' Attitudes Towards Deprescribing (rPATD) questionnaire was developed by Reeve et al [22] to capture attitudes and beliefs towards deprescribing among older adults and caregivers. This original English questionnaire was used internationally in different countries and settings, and was translated if needed in different languages [23][24][25][26][27][28]. Previous international studies have reported older adults' and caregivers' openness to deprescribing, but few have concurrently assessed older adults' and caregivers' attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…There is conflicting evidence regarding the association of the number of medications with willingness to deprescribe. Some studies reported a significant association [ 33 , 34 ] similar to our findings whilst others have shown no significant association [ 30 , 31 , 35 , 36 ]. This difference might be due to differences in the population characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous community based studies, participants in our study reported a greater desire to be involved in decision-making [ 30 ]. This contrasts a study conducted in inpatient setting in the UK, where participants had a lower desire to be involved in decision-making [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…A recent systematic review showed high patient satisfaction toward pharmacist-led medication review interventions ( Bou Malham et al, 2021 ). In addition, patients showed a positive attitude toward pharmacists’ competencies and involvement in deprescribing, especially the elderly ( Bužančić et al, 2021 ). Further, a study reported that patient satisfaction could be enhanced by deprescribing as patients felt uncomfortable with the use of multiple medications ( Reeve et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%